The comparison of site spider “biodiversity quality” in Portuguese protected areas - Feest, Alan; Cardoso, Pedro (Ecological Indicators, 2012)
Spiders at 23 Portuguese protected area sites were sampled (pitfall trapped) over 10-month periods. The data allowed for a “biodiversity quality” assessment consisting of the following indices: Species Richness, Biomass, Simpson Index, Species Conservation Value Index and Population Density. These “biodiversity quality” characteristics were reviewed for relative indication of site spider “biodiversity quality”. Spiders are proposed as a group of organisms that could be used to indicate part of the “biodiversity quality” of a site since they can be sampled in a standardised way and yield biodiversity indices for comparison spatially and temporally. The approach adopted in this paper allows a range of “biodiversity quality” indices to be measured for spiders in Portuguese protected areas which, in turn requires decisions from scientists, managers and politicians on what element or characteristic of biodiversity it is intended to be targeted.
Keywords: biomass; Simpson Index; Site ranking; Species Conservation Value Index (SCVI); Species richness